The Analysis of the Business Strategy of Hizzy Joy'S Here Coffee Shop in Medan City - Azhari, Fauzan ridho; Safitri, Sri Ariani (Jurnal Agriuma, 2025)
The rapid growth of coffee shops in Medan City has intensified competition, causing some businesses to close due to their inability to compete. This study analyzes the business strategy of Coffee Shop Hizzy Joy’s Here by identifying internal and external factors and formulating appropriate strategies to enhance competitiveness. The research employs Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), SWOT analysis, and the IE Matrix. The results show an IFE score of 3.28, indicating key strengths in product quality, service, comfortable ambiance, and adequate facilities, with weaknesses in parking space and pricing competitiveness. The EFE score of 3.93 reflects the ability to utilize opportunities such as a strategic location and the growing coffee trend, while remaining resilient to threats like tight competition and raw material price fluctuations. The IE Matrix places the business in Quadrant I (Grow and Build), suggesting strategies of market penetration, product development, and technology utilization. Overall, Coffee Shop Hizzy Joy’s Here has strong potential to grow and maintain its competitive advantage in Medan’s coffee shop industry.